Krylov complexity in the Schrödinger field theory - Peng-Zhang He; Hai-Qing Zhang (Journal of High Energy Physics)
Abstract We investigate the Krylov complexity of Schrödinger field theories, focusing on both bosonic and fermionic systems within the grand canonical ensemble which includes a chemical potential. Krylov complexity measures operator growth in quantum systems by analyzing how operators spread within the Krylov space, a subspace of the Hilbert space spanned by successive applications of the superoperator [H, ·] on an initial operator. Using the Lanczos algorithm, we construct an orthonormal Krylov basis and derive the Lanczos coefficients, which govern the operator connectivity and thus characterize the complexity. Our study reveals that the Lanczos coefficients {b n } are almost independent of the chemical potential, while {a n } are dependent on the chemical potential. Both {a n } and {b n } show linear relationships with respect to n. For both bosonic and fermionic systems, the Krylov complexities behave similarly over time, especially at late times, due to the analogous profiles of the squared absolute values of their autocorrelation functions |φ 0(t)|2. The Krylov complexity grows exponentially with time, but its asymptotic scaling factor λ K is significantly smaller than the twice of the slope of the {b n } coefficients, contrasting to the relativistic field theories where the scaling aligns more closely with the twice of the slope of {b n }.